Essai de biocontrôle de Fusarium sp.agent de la pourriture sèche des agrumes(Citrus) par des extraits d’Atriplex halimus. - SLAMNIA, Halima; KIROUANE, Fatiha (My University, 2024)
The objective of the work carried out is to evaluate the effectiveness of an endemic aromatic plant, Atriplex halimus, in the fight against dry rot of citrus fruits caused by the pathogen Fusaruim sp. This plant of the Chenpodiaceae family (amaranthaceae), is rich in phenolic compounds. To extract the latter, we used four extraction methods; Soxhlet, maceration in ethanol, maceration in acetone and essential oil.The results of the "in vivo" test demonstrate the protective effect of extracts from the plant of Atriplex halimus on the roots of orange trees.
Keywords: Fusariumsp; Atriplexhalimus; extract; maceration; Soxhletgrowth; sporulation